VISUAL AND COGNITIVE MEDIA: THE LANGUAGE ACQUISITION OF CHILDREN WITH DYSLEXIA IN ACEH - Nina Afrida; Rita Mahriza; Meutia Rahmah; Nani Endri Santi (State Islamic University of North Sumatra Indonesia, 2019)
This paper aims at revealing the causal-effect relationship between picture and dyslexia’s reading ability when acquiring the language and describing their behavior when picture is applied as a media in learning reading. Single subject used as a research design here by observing students’ behavior when trying to obtain the language using a negative picture and testing them with an Oral reading test. Three Acehnese children 7-9 years intermediate classes were chose as the sample. The result showed that dyslexia’s ability was effected by picture significantly